2009
DOI: 10.1182/blood-2008-10-187203
|View full text |Cite
|
Sign up to set email alerts
|

Microarray-based classifiers and prognosis models identify subgroups with distinct clinical outcomes and high risk of AML transformation of myelodysplastic syndrome

Abstract: The diagnosis of myelodysplastic syndrome (MDS) currently relies primarily on the morphologic assessment of the patient's bone marrow and peripheral blood cells. Moreover, prognostic scoring systems rely on observer-dependent assessments of blast percentage and dysplasia. Gene expression profiling could enhance current diagnostic and prognostic systems by providing a set of standardized, objective gene signatures. Within the Microarray Innovations in LEukemia study, a diagnostic classification model was invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
144
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(150 citation statements)
references
References 37 publications
(48 reference statements)
4
144
0
2
Order By: Relevance
“…Acute myeloid leukemia (AML), a deadly form of hematopoietic malignancies, is a group of heterogeneous diseases with considerable diversity in terms of clinical behavior and prognosis, it is the most common malignant cancer in children and young people (Weltermann et al, 2004;Pasqualucci et al, 2006;Falini et al, 2007;Mills et al, 2009;Burnett et al, 2011). Gene-expression detection technology in the hematopoietic cell of AML patients have been applied in scientific research and clinical testing, in hope of identifying candidate genes which may refer to the development and progression of AML and marker of diagnosis or prognosis (Delaunay et al, 2003;Weltermann et al, 2004;Gonzalez Garcia et al, 2006;Foran, 2010;Flach et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Acute myeloid leukemia (AML), a deadly form of hematopoietic malignancies, is a group of heterogeneous diseases with considerable diversity in terms of clinical behavior and prognosis, it is the most common malignant cancer in children and young people (Weltermann et al, 2004;Pasqualucci et al, 2006;Falini et al, 2007;Mills et al, 2009;Burnett et al, 2011). Gene-expression detection technology in the hematopoietic cell of AML patients have been applied in scientific research and clinical testing, in hope of identifying candidate genes which may refer to the development and progression of AML and marker of diagnosis or prognosis (Delaunay et al, 2003;Weltermann et al, 2004;Gonzalez Garcia et al, 2006;Foran, 2010;Flach et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…97 HOX gene abnormalities have been implicated in fusions giving rise to myeloid malignancies, as described below. GEP of MDS patients show HOX deregulation with high risk of transformation to AML 98 and that HOX upregulation is associated with poor prognosis AML, 99 although no study has yet correlated the deregulation of HOX genes with SF3B1 mutations. However, the study in mouse 97 shows that SF3B1 spliceosomal protein is required to repress HOX genes, so there may well be a link between these two genes in the context of human disease, as predicted by the mouse model.…”
Section: Spliceosomal Mutationsmentioning
confidence: 99%
“…GEP is highly accurate in predicting cytogenetically favorable AML subtypes, such as core-binding factor (CBF-AML) and acute promyelocytic leukemias. However, it is less accurate in predicting intermediate and high risk cytogenetic subtypes (such as monosomy 7 and 11q23) [13] with the exception of FLT3-ITD, where gene expression signatures using mRNA microarrays were found to outperform FLT3-ITD mutation status in predicting disease outcome, thereby supporting the use of GEP in these cases [14][15][16]. Moreover in older adults, GEP studies revealed signatures that were unique and distinct from those of younger patients and suggestive of a different biology [17].…”
Section: Molecular Diagnostic In Aml Gene Mrna Expression Microarraysmentioning
confidence: 99%
“…These proteins can bind GTP and GDP, and they have intrinsic GTPase activity. Activating mutations of RAS, either KRAS or NRAS, constitute approximately 20% of detected mutations in AML [98], especially in CBF-AML (particularly inv (16)). However, they do not appear to carry any major prognostic significance in terms of DFS, EFS or OS [3,99].…”
Section: Rasmentioning
confidence: 99%